Role of Private Institutions in Maximizing ESL Learning Conditions in the Thenmaradchi Zone - Mathursha, K.; Paranthaman, V. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
In the twenty-first century, the English language holds immense global significance, both in everyday communication and across diverse academic, professional, and technological domains. Often described as a global lingua franca, English has become the most widely spoken second language worldwide. Within this context, private institutions play a pivotal role in supporting and enhancing English as a Second Language (ESL) learning. This research proposal seeks to examine the study programs, facilities, and contributions of private institutions in optimizing ESL learning conditions. The study emphasizes the importance of equipping learners with effective approaches to English language acquisition, thereby fostering higher levels of proficiency and communicative competence. The research adopts a qualitative methodology, utilizing carefully designed questionnaires, informal interviews, and direct observations to collect data. Through these methods, the study evaluates the effectiveness of the programs offered by private institutions. Specifically, it explores how innovative teaching strategies, personalized learning approaches, access to modern technology, and smaller class sizes contribute to creating more effective ESL learning environments in the Thenmarachchi zone. This study reveals that the researcher aims to provide practical recommendations to strengthen the teaching and learning practices of private institutions. Ultimately, the findings are expected to contribute to the advancement of English language learning among students and to support the development of more effective ESL pedagogy in the future.
Keywords: Private institutions; ESL learning; Learning environments; Personalized learning; Language proficiency; ESL learners; Language teaching; Global language